Memory, Migration and (De)Colonisation in the Caribbean and Beyond (University of London Press, 2021)
In recent years, academics, policy makers and media outlets have increasingly recognised the importance of Caribbean migrations and migrants to the histories and cultures of countries across the Northern Atlantic. Memory, Migration and (De)Colonisation furthers our understanding of the lives of many of these migrants, and the contexts through which they lived and continue to live. In particular, it focuses on the relationship between Caribbean migrants and processes of decolonisation. The chapters in this book range across disciplines and time periods to present a vibrant understanding of the ever-changing interactions between Caribbean peoples and colonialism as they migrated within and between colonial contexts. At the heart of this book are the voices of Caribbean migrants themselves, whose critical reflections on their experiences of migration and decolonisation are interwoven with the essays of academics and activists.